Analisis Implementasi Monitoring dan Evaluasi dalam Pencegahan Korupsi di Pemerintah Kota Kupang - Pattimau, Andrianus (Jurnal Ilmiah Global Education, 2024)
Corruption is a serious issue that negatively impacts development and public trust in government. This study aims to analyze the implementation of monitoring and evaluation in corruption prevention in the Kupang City Government over the 2021-2023 period. The method used is a descriptive qualitative approach, with data collection through in-depth interviews, document analysis, and observation. The results of the study indicate that the Monitoring Center for Prevention (MCP) score of the Kupang City Government fluctuated during the study period, with a decline in 2022 and a significant increase in 2023. Factors affecting the effectiveness of corruption prevention include internal management, technological infrastructure, government regulations, and external partnerships. Although there have been some improvements, major challenges include budget and human resource constraints, a lack of employee understanding of the importance of monitoring and evaluation, and resistance to organizational culture change. The study recommends increasing budget allocation and human resources, intensive training for employees, cultural change toward transparency and accountability, and strengthening partnerships with external institutions. Furthermore, routine evaluation and continuous improvement should be implemented to ensure the effectiveness of corruption prevention in the future.